Healthcare Provider’s General Perception and Attitude toward Pharmacists in Saudi Arabia - Alomi, Yousef Ahmed; Al-Hathlool, Sarah Abdullah; Albadi, Marzooq Abdullah Marzooq; Almulhim, Maryam Ibrahim; Aboshalaf, Yousef; Al-Ethan, Mytham (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the Healthcare professionals’ perception and attitude towards pharmacists in Saudi Arabia. Methods: It is a 4-month cross-sectional survey of healthcare professionals’ perception towards pharmacists. The survey consisted of two-part of demographic information and second part forty-nine questions divided into four domains. It included domain one: healthcare providers general perception of pharmacist domain 2: Healthcare professionals’ perception of pharmaceutical care services, domain 3: healthcare professionals’ perception of visiting ambulatory care and domain 4: Healthcare professionals’ perception of pharmacists’ relationship and counseling. All types of healthcare professionals included in the study. The 5-point Likert response scale system was used. The questions were open and close-ended. The survey was distributed through social media by using WhatsApp to more than one thousand healthcare professionals overall the Kingdom of Saudi Arabia. The survey was made as an electronic format and it analyzed and discussed domain one: healthcare providers’ general perception of pharmacist through monkey survey system. Results: The total responders were (170) healthcare providers. Of those 150 (93.8%) were Saudi and 10 (6.25%) were non-Saudi. The gender distribution was 129 (75.9%) females and 41 (24.1%) were males. The majority of patient visited the pharmacy in the past 12-months more than ten times were 53 (31.36%) while 40 (23.67%) attended as visitors for 5-9 times. Most of the patient (143 (87.2%)) spent less than 16 minutes waiting for the medication at the pharmacy. The statement said by pharmacists with highest score was “the pharmacist had the significant role in preventing medications errors (4.76), pharmacy job is vital in our society (4.74), the pharmacist participates in patient therapeutic plan as part of the medical team (4.5)”. Also, the pharmacist is the first person to be asked about medications (4.47), Healthcare professionals know the clinical pharmacist and his role in patients’ care (4.47). More than 60% of healthcare professionals will choose the pharmacy as specialty or suggest to the family members or friend to select the pharmacy as their profession. Most of the healthcare providers visited the pharmacy as the pharmacist knows more about drug doses and adverse drug reaction 98 (58.33%) and the to seek pharmacists help in general health illness (96 (57.14%)). Other reason for visiting the pharmacy to get free consultation (49 (29.17%)) and since there is no need to have an appointment for pharmacy visit (48 (28.57%)). Also, most of the healthcare professionals refused to utilize the pharmacy just for cosmetics (118 (70.23%)). Conclusion: Most of the healthcare professionals had a real perception towards the pharmacist and his role in preventing medication errors and sharing in the therapeutic plan. The pharmacist should expand clinical pharmacy services at all healthcare institutions in Saudi Arabia since there is an acceptance for such concept.
Keywords: Healthcare Provider; Perception; Attitude; Pharmacists; Ministry of Health; Saudi Arabia